1970
DOI: 10.3329/bjar.v36i3.9266
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Preserved Seeds Using Different Botanicals On Seed Quality Of Lentil

Abstract: Laboratory studies were conducted with leaf powder of three plants to show the preservative effect for maintaining the quality of lentil seeds in storage. After processing and drying, seeds were preserved with different botanicals and stored them in earthen pots for eight months. Botanicals, such as whole leaf powder of neem (Azadirachta indica), dholkalmi (Ipmoea sepiara), and bishkatali (Polygonum hydropiper) were used at a dose of 5% w/w (25 g botanical per 500 g of lentil seeds). The lentil seeds were stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…, Keshavulu and Krishnasamy (2005), and Khatun et al, (2011) recorded similar results with botanicals in different crops. Therefore farmers may use botanicals for the management of stored grain pests without any adverse effect on germination (Mamun and Shahjahan, 2011;Ogendo et al, 2004), viability and vigour of the treated seeds.…”
Section: Effect Of Biopesticides (Botanicals) On Seed Qualitysupporting
confidence: 60%
“…, Keshavulu and Krishnasamy (2005), and Khatun et al, (2011) recorded similar results with botanicals in different crops. Therefore farmers may use botanicals for the management of stored grain pests without any adverse effect on germination (Mamun and Shahjahan, 2011;Ogendo et al, 2004), viability and vigour of the treated seeds.…”
Section: Effect Of Biopesticides (Botanicals) On Seed Qualitysupporting
confidence: 60%
“…The success of pelleting depends on the selection of filler material. Researchers expressed the beneficiary influence of different filler material such as leaf powder (Khatun et al, 2011), biofertilizer (Selvakumar et al, 2012), biocontrol agents (Nargis, 1995) inorganic nutrients (Lu et al, 1983), vermicompost (Mathivanan et al, 2012) and combination of all these for obtaining improved planting value. In the present investigation, the redgram seeds were pelleted with organic powders of noni, tulasi and gallnut (Table 1) recorded highly significant difference among the seed pelleting treatment at initial laboratory evaluation…”
Section: Resultsmentioning
confidence: 99%
“…Seed quality is the prerequisite for improving germination and yield of crop plants, which can be improved through seed management techniques (Khatun et al, 2011). Seed management techniques not only invigorate the seed but also modify the physical and biochemical characteristics of seed and aid in improving its productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Abdulaziz et al 14 found that storage of Ephedra alta seeds in cotton cloth bags favorably maintained seed moisture content below critical level resulting in minimum seed deterioration compared with other seed storage containers. Khatun et al 15 used botanicals, such as whole leaf powder of neem (A.indica), Dholkalmi (Ipomoea sepiara), and Bishkatali (Polygonum hydropiper) at a dose of 5% w/w (25 g botanical per 500 g of lentil seeds), A. indica. In addition, P. hydropiper were effective in preserving seed germination and seed vigor of lentil.…”
Section: Resultsmentioning
confidence: 99%